2021
DOI: 10.15585/mmwr.mm7022e1
|View full text |Cite
|
Sign up to set email alerts
|

Patterns in COVID-19 Vaccination Coverage, by Social Vulnerability and Urbanicity — United States, December 14, 2020–May 1, 2021

Abstract: Disparities in vaccination coverage by social vulnerability, defined as social and structural factors associated with adverse health outcomes, were noted during the first 2.5 months of the U.S. COVID-19 vaccination campaign, which began during mid-December 2020 (1). As vaccine eligibility and availability continue to expand, assuring equitable coverage for disproportionately affected communities remains a priority. CDC examined COVID-19 vaccine administration and 2018 CDC social vulnerability index (SVI) data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
157
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 170 publications
(172 citation statements)
references
References 5 publications
13
157
2
Order By: Relevance
“…Equitable access to vaccination is critical to improve coverage for persons of all ages who live in communities that are less urban ( 6 ), have higher social vulnerabilities ( 1 , 7 ), and have higher percentages of social determinants of poor health ( 8 ). In a report that pooled findings from two representative surveys of U.S. adults aged 18–39 years, only one half (51.8%) reported that they had been or were planning to be vaccinated, whereas 24.9% reported that they probably or definitely would not be vaccinated, and 23.2% reported that they would probably be vaccinated or were unsure if they would be vaccinated ( 9 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Equitable access to vaccination is critical to improve coverage for persons of all ages who live in communities that are less urban ( 6 ), have higher social vulnerabilities ( 1 , 7 ), and have higher percentages of social determinants of poor health ( 8 ). In a report that pooled findings from two representative surveys of U.S. adults aged 18–39 years, only one half (51.8%) reported that they had been or were planning to be vaccinated, whereas 24.9% reported that they probably or definitely would not be vaccinated, and 23.2% reported that they would probably be vaccinated or were unsure if they would be vaccinated ( 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…Second dose completion was defined as the percentage of persons who received the second dose of a 2-dose vaccine at any point, among those who had received at least 1 dose of a 2-dose vaccine. *** Absolute differences in coverage by age were calculated during three periods selected to represent general shifts in targeted subpopulations, supply, and policy over the course of the COVID-19 vaccination program ††† ( 1 ): December 14, 2020–January 23, 2021; January 24, 2021–March 20, 2021; and March 21, 2021–May 22, 2021.…”
mentioning
confidence: 99%
“…Taken together, the findings of this study make clear that ensuring equitable access to COVID-19 vaccination should be a priority for the U.S. COVID-19 vaccination program. Early evidence suggests that vaccination has been lower among residents of counties with disadvantaged social conditions [57,58]. This may be due to limited vaccination supply, difficulty taking time off from work, or higher rates of mistrust of the medical system and vaccine hesitancy [59].…”
Section: Plos Onementioning
confidence: 99%
“…28 The CDC recently published its findings that most socially vulnerable communities have vaccinated 11% fewer adults than least vulnerable counties. 29 Many have focused on the role of vaccine hesitancy in explaining heterogeneity in vaccine uptake 8,30 , however, our findings suggest that there are additional systemic barriers that must be addressed alongside. The CVAC offers policymakers a broader picture of supply-and demandside factors to overcome barriers within their jurisdictions.…”
Section: Discussionmentioning
confidence: 78%